Diet of direct-developing frogs (Anura: Craugastoridae: Pristimantis) from the Andes of western Colombia (2015)
We studied the diet of 15 montane frog species of the genus Pristimantis (Craugastoridae) from the Andes of Western Colombia to determine the diet range, breadth of niche and overlap among species. We identified 499 prey items from stomach and intestinal contents of 154 specimens. Prey items were included in 74 different categories. The most common 15 prey categories accounted for 65 % of all frogs’ diet. The invertebrate families Isotomidae, Chironomidae, Formicidae, and Tipulidae were the most abundant categories and accounted for 32 % of the frogs’ diet. Ten of the 15 frog species were found with at least one item of Araneae. Coleoptera and Tipulidae were found in nine frog species, and Acari and Carabidae in eight frog species. In general, beetles were found in gastrointestinal tracts of all species examined, except for P. quantus, but interpretation needs caution because only one individual of this species was caught. Pristimantis hectus showed a specialized diet, consuming mainly dipterans of the family Chironomidae, while the remaining species showed a generalist diet. Pristimantis palmeri showed niche overlap with P. erythropleura (Ф jk = 0.69), P. myops (Ф jk = 0.64), and P. orpacobates (Ф jk = 0.64). Our results suggest that most of the frogs species studied are generalist, foraging opportunistically on dipterans, arachnids, collembolans, coleopterans, and hymenopterans. Here, we report the diet of montane Pristimantis species and discuss the results in comparison with data on related species in montane and lowland regions